PRACTICAL DEVELOPMENT OF ANDROID-BASED INTERACTIVE LEARNING MEDIA USING SMART APPS CREATOR (SAC) ON MEASUREMENT MATERIALS - Komariah, Siti; Ariani, Tri; Gumay, Ovilia Putri Utami (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This research is motivated by students’ understanding of physics learning material is still lacking and the lack of learning media and the lack of student creativity in finding learning resources. The purpose of this study is to develop an Android-based interactive learning media using Smart Apps Ceator (SAC) on practical measurement materials. This research is an R&D development research (Research and Development) using a 4-D development model consisting of Definition, Design, Development and Dissemination. At the Development stage there is a practicality test and the subjects of this research are physics teachers and students. The results of the practicality test that have been obtained are with a practicality score of 86% for the practicality test of physics teachers with very practical criteria, a practicality score of 88.4% is obtained for small group practicality trials and a practicality score of 92 is obtained, 2% for the practicality trial of a large group (field group) with very practical criteria. So it can be concluded that android-based interactive learning media using Smart Apps Creator (SAC) on measurement material through practicality tests with the practicality test assessment questionnaire instrument that has been carried out has met the very practical criteria so that it is feasible to be used for students in the learning process.